Abiotic parameters measured in surface sediments along south-east Queensland, Australia - Dissanayake, Navodha G; Frid, Christopher L J; Caswell, Bryony A (In: Dissanayake, NG et al. (2020): Biodiversity, trait composition and ecological functioning: impacts of coastal urbanisation on subtropical mudflats [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.915865, 2020)
Sites were located between south Deception Bay and Tallebudgera, Gold Coast. Sampling was carried out in winter 2016 (July-August) and summer 2017 (January-February). The 24 sites were categorised into four land-use sub-catchments e.g. high industry, low industry, residential and peri-urban (see paper for categories and site classifications). Sediment properties such as the redox discontinuity layer (RDL) depth (measured five times from each box core using a ruler (to the depth of the black anoxic layer)), organic matter content (as percentage on loss on ignition; measurements were made on homogenised sediment from three cores (diameter 4 cm) collected at each smapling site, cores were extracted to 11 cm sediment depth) and the proportion of silt and clay sized particles (in the top 11cm) and benthic chlorophyll a concentration (three samples were collected from the sediment surface (to 2cm depth) , at close proximity (2 cm) to the extracted box core area) were measured in triplicate to describe each site with respect to urban gradients.
Keywords: Biological traits; ecosystem dynamics; intertidal; Macrofauna; south east Queensland